Rhymes and jingles / by Mary Mapes Dodge. - Dodge, Mary Mapes, 1830-1905. (Tufts University. Tisch Library., 2016)
1 online resource (xii, 271 pages) : illustrations.; Decorative cloth cover, stamped in black and gold.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.